A criação da Faculdade de Sciencias Juridicas e Sociaes de Manáos pelo olhar dos periódicos acadêmicos, 1909-1927 - Araújo, Cristina da Silva (Brasil, 2024)
The present study addresses the origins and early years of the Faculdade de Sciencias Juridicas e Sociaes de Manáos through the eyes of academic journals from the Amazon from the 1909s to the 1920s. position of the academic press about this process. The methodology used is the analysis of journals, combined with the concept of memory, contextualized under a social and cultural history approach. The study concluded that the Faculty was the result of the historical context of the Belle Époque of Manaus, fulfilling the ideals of an intellectual elite regarding the modernization of the Amazonian capital.